Are European banks in economic harmonay? An HLM aproach - James P. Gander (The University of Utah, Department of Economics, 2012)
A reduced-form equation relating the log of the capital account ratio to several micro and macro variables, particularly the profitability variable, for the commercial banks in nine European countries over eleven years, 1991-2001, was constructed. The equation consisted of a fixed-effects part and a random-effects part. The Hierarchical Linear Model (HLM) approach was used to test the harmonization hypothesis relating the capital account ratio to the profit rate across the countries and over the years. The statistical results indicated that while some differences in bank behavior as indicated by the intercept and slope deviations across countries and over years did exist, by and large, most of the differences or deviations from the fixed-effects means were not significantly different from zero. The harmonization hypothesis was accepted. European bank behavior gave evidence of being in harmony and uniform over countries and years. Some policy implications are discussed briefly.
Keywords: C23; C40; C51; G21; G28; 330; Bank behavior; Profit; Capital account ratios; Harmonization